Blast-Related Mild TBI Alters Anxiety-Like Behavior and Transcriptional Signatures in the Rat Amygdala - Blaze, Jennifer; Choi, Inbae; Wang, Zhaoyu; Umali, Michelle; Mendelev, Natalia; Tschiffely, Anna E.; Ahlers, Stephen T.; Elder, Gregory A.; Ge, Yongchao; Haghighi, Fatemeh (Frontiers in Behavioral Neuroscience, 2020)
The short and long-term neurological and psychological consequences of traumatic brain injury (TBI), and especially mild TBI (mTBI) are of immense interest to the Veteran community. mTBI is a common and detrimental result of combat exposure and results in various deleterious outcomes, including mood and anxiety disorders, cognitive deficits, and post-traumatic stress disorder (PTSD). In the current study, we aimed to further define the behavioral and molecular effects of blast-related mTBI using a well-established (3 x 75 kPa, one per day on three consecutive days) repeated blast overpressure (rBOP) model in rats. We exposed adult male rats to the rBOP procedure and conducted behavioral tests for anxiety and fear conditioning at 1-1.5 months (sub-acute) or 12-13 months (chronic) following blast exposure. We also used next-generation sequencing to measure transcriptome-wide gene expression in the amygdala of sham and blast-exposed animals at the sub-acute and chronic timepoints. Results showed that blast-exposed animals exhibited an anxiety-like phenotype at the sub-acute timepoint but this phenotype was diminished by the chronic timepoint. Conversely, gene expression analysis at both sub-acute and chronic timepoints demonstrated a large treatment by timepoint interaction such that the most differentially expressed genes were present in the blast-exposed animals at the chronic timepoint, which also corresponded to a Bdnf-centric gene network. Overall, the current study identified changes in the amygdalar transcriptome and anxiety-related phenotypic outcomes dependent on both blast exposure and aging, which may play a role in the long-term pathological consequences of mTBI.